การศึกษาพฤติกรรมการเสริมแรงของรากพืชเพื่อป้องกันการพังทลายของลาดดิน - อดิเทพ วังบุญคง (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Landslide is one of major disasters in Thailand, especially in the rural slope area. Landslide can affect and disrupt agriculture, housing and transportation routes. The government spends a lot of the annual budget for solving this problem. Recently, a royal project of His Majesty the King’s initiative on the use of vetiver grass for soil and water conservation is promoted and implemented by government and non-government sectors. In agriculture, the vetiver root system is believed that it could penetrate deeply into the ground to form a net-like barrier capable of filtering soil particle to protect soil erosion. Therefore, this research aims to study the effect of vetiver root on shear strength of soil. The highland and lowland species of the free-growth vetiver specimens were grown in 2, 4 and 6 months. The vetiver specimens were prepared in a single root for the direct shear box test and in a group for the large direct shear test. The results of direct shear tests can be used to interpret the shear strength parameters of the vetiver reinforced soil (i.e., cohesion and angle of internal friction). The root structure of vegetation can simply be defined by a root-area ratio number. In this study, an image processing technique was employed to determine the root-area ratio of the vetiver specimens. Moreover, a simple slope failure problem was modelled using SLOPE/W software. The results indicated that the vetiver root can increase the shear strength of soil approximately 5 – 9% and 10 – 13% for single root and group vetiver, respectively. The maximum root-area ratio of 4.56% and the root length of 1.8 m were observed on the 6-months growth vetiver specimen. In addition, the vetiver root can increase the factor safety of slope only 1.2% in the severe case of high water table.